Linseed Oil Nanoemulsions for treatment of Atopic Dermatitis disease: Formulation, characterization, in vitro and in silico evaluations - Kildaci, Ilke; Budama-Kilinc, Yasemin; Kecel-Gunduz, Serda; Altuntas, Ebru (ELSEVIER, 2021)
Atopic Dermatitis (AD) is a chronic skin disease that is characterized by inflammation, dryness and bacterial infection accompanied by immunological changes and develops with the deterioration of the barrier property of the skin. The aim of this study is to prepare and characterize the innovative nanoemulsion (NE) formulations containing Linum usitatissimum seed (linseed) oil (LSO) and to investigate their potential with in vitro and in silico evaluation for the treatment of AD. In this study, LSO-NE formulations were prepared by ultrasonic emulsification method. Initially, the kinetic and thermodynamic stability of the LSO-NE formulations were studied using accelerated stability tests in terms of any physical instability problems such as creaming, sedimentation, coalescence, and phase separation. Following the heating cooling test for 6 cycles, the stable LSO-NE formulations were stored at three different storage conditions (25 +/- 2 degrees C and 60% RH, 40 +/- 2 degrees C and 75% RH, and 5 +/- 3 degrees C) for 60 days to study the physicochemical stability. LSO-NE formulation with the highest stability and suitable physicochemical properties was considered for topical application. In vitro Ames/Salmonella assay was used for determination of the mutagenicity of LSO-NE formulation. Also, by molecular docking analysis, the binding affinities and binding orientations of the active ingredients in LSO to the target (HLA) molecules were determined, and their activities were estimated by means of their interaction mechanisms using in silico modelling. As a result of the physicochemical stability tests, the formulation encoded with F4P1 was the most durable formulation among them with a mean droplet size of 99.02 +/- 1.06 nm, a PdI value of 0.14 +/- 0.020, and a zeta potential value of -8.79 +/- 0.034 mV. It was determined that the optimum NE formulation released 78.4% of the LSO at the end of 24 h, and 100% of LSO within 48 h. It showed no mutagenic effect on TA98 and TA100 strains of Salmonella typhimurium. In the light of our molecular docking and ADMET calculations, it was determined that LSO will be a potential drug candidate for AD treatment.
Keywords: Nanoemulsion; Topical; Linseed oil; Atopic dermatitis; Linum usitatissimum; Molecular docking; LINUM-USITATISSIMUM; LOADED NANOEMULSION; ACCURATE DOCKING; NANO-EMULSIONS; EUCALYPTUS OIL; AMES TEST; FLAXSEED; ECZEMA; MANAGEMENT; STABILITY; Pharmacology & Pharmacy